Using modeling and rehearsal to teach fire safety to children with autism. Issue 3 (30th June 2016) - Garcia, David; Dukes, Charles; Brady, Michael P.; Scott, Jack; Wilson, Cynthia L.
Abstract : We evaluated the efficacy of an instructional procedure to teach young children with autism to evacuate settings and notify an adult during a fire alarm. A multiple baseline design across children showed that an intervention that included modeling, rehearsal, and praise was effective in teaching fire safety skills. Safety skills generalized to novel settings and maintained during a 5‐week follow‐up in both training and generalization settings.